Crowdfunding’s Potential in the Caribbean : A Preliminary Assessment - World Bank (World Bank, Washington, DC, 2019)
Among the multitude of barriers to growing businesses, access to finance is a principal challenge faced by Caribbean enterprises. infoDev’s Entrepreneurship program for innovation in the Caribbean (EPIC) Access to finance component aims to develop an innovative access to finance program for growth-oriented Caribbean entrepreneurs. The focus is on building the pipeline of investment-ready enterprises through training and mentoring, as well as strengthening investors’ overall capacity to engage in innovative financing mechanisms, such as angel investing and crowdfunding. Over the past few years, there has been experimental use of crowdfunding by existing small and medium enterprises (SMEs) and start-ups in the Caribbean. Crowdfunding leverages Internet technology and offers a new path to capital formation that may mitigate some challenges, including geographic isolation and the limited size of local addressable customer and capital markets. This report’s scope is a preliminary assessment of the potential viability of crowdfunding in the Caribbean, which serves as an initial step for further research. This study presents recommendations for developing the framework for crowdfunding in the Caribbean that can benefit both existing SMEs as well as start-ups.